Plant Proteoforms Under Environmental Stress: Functional Proteins Arising From a Single Gene - Kosová, Klára; Vítámvás, Pavel; Prášil, Ilja Tom; Klíma, Miroslav; Renaut, Jenny (Frontiers in Plant Science, 2021)
Proteins are directly involved in plant phenotypic response to ever-changing environmental conditions. The ability to produce multiple mature functional proteins, i.e., proteoforms, from a single gene sequence represents an efficient tool ensuring diversification of protein biological functions underlying the diversity of plant phenotypic responses to environmental stresses. Basically, two major kinds of proteoforms can be distinguished: protein isoforms, i.e., alterations at protein sequence level arising from posttranscriptional modifications of a single pre-mRNA by alternative splicing or editing, and protein posttranslational modifications (PTMs), i.e., enzymatically catalyzed or spontaneous modifications of certain amino acid residues resulting in altered biological functions (or loss of biological function such as in non-functional proteins arised as a product of spontaneous protein modification by reactive molecular species RMS). Modulation of protein final sequence resulting in different protein isoforms as well as modulation of chemical properties of key amino acid residues by different PTMs (including phosphorylation, N- and O-glycosylation, methylation, acylation, S-glutathionylation, ubiquitinylation, sumoylation, modifications by reactive molecular species RMS) thus represents an efficient means to ensure flexible modulation of protein biological functions in response to ever-changing environments. The aim of the present review is to provide a basic overview on structural and functional diversity of proteoforms derived from a single gene in the context of plant evolutional adaptations underlying plant responses to variability of environmental stresses, i.e., adverse cues mobilizing plant adaptive mechanisms to diminish their harmful effects.